The Internet at the Service of Society: Business Ethics, Rationality, and Responsibility - González, Wenceslao J. (ENDOXA, 2020)
Serving the community is what the Internet — in the broad sense — does in many ways, within the knowledge society. The layers of its ontological structure — technology infrastructure, the Web, and the cloud computing and practical applications (apps) — are in principle at the service of society. This service is carried out by companies, which are ethically assessable insofar as they are “social subjects.” Their public service purpose at the three layers during the coronavirus lockdown is considered here. Within a framework of business ethics, this article looks deeply at companies as “social subjects.” They contribute decisively to a multilayered reality that reaches half of the world's population. The analysis of this network of networks is carried out through rationality and responsibility. Thus, this paper analyzes its ethical responsibility based on the social ontology of business firms and the ethical problems according to the kind of rationality involved in the companies — micro, meso or macro — in accordance with their goals. Then, from the perspective of service to society, this study reflects on business ethics of the Internet — in the broad sense — in two directions: 1) the need for evaluative rationality or rationality of ends, because instrumental rationality or rationality of means is insufficient for ethics, and 2) the importance of combining individual responsibility with social responsibility.